Intelligent quotient, emotional intelligence and spiritual intelligence as correlates of prison adjustment among inmates in Nigeria prisons (2010)
The study investigated the extent to which intelligent quotient, emotional intelligence and spiritual intelligence would jointly and relatively predict prison-adjustment among Nigerian prisoners. The participants were five hundred prisoners randomly selected from five prisons in Nigeria. They are made up of four hundred and fifty eight males and forty-two females. The study utilized expost facto correlational research design. Multiple regression analysis and pearson product moment correlation were was used to analyse data collected to test the three research questions raised in the study. The results showed significant positive correlations between the independent variables and prison adjustment with emotional intelligence taking the lead (r = 0.95), followed by spiritual intelligence (r = 0.83) and lastly, intelligent quotient (r = 0.79). Also, the three independent variables contributed a total of 93.2% to the criterion (Prison Adjustment), while relative contributions as revealed by the Beta results showed Emotional Intelligence (B = 0.736), Spiritual Intelligence (B = 0.443) and Intelligent Quotients (B = 0.173). On the basis of the findings, it was recommended that prisoners should be exposed to emotional intelligence training as well as regular, functional religious programmes to enhance their effective adjustment. It was therefore concluded that emotional intelligence and spiritual intelligence skills are far more important than intelligent quotient. Therefore instead of placing more emphasis on being brilliant, let students and people who demonstrate high level of emotional intelligence and spiritual intelligence be properly encouraged